Unlike Phoenix from the ashes : Republican constructs of the First World War in Weimar Germany 1918-1920 - Ther, Vanessa (Trinity College (Dublin, Ireland). Department of History, 2010)
This thesis seeks to examine the utilisation of the legacy of the First World War in republican press and propaganda as a central focus of the new state’s foundation narrative. Assessing the role of the war in republican attempts to establish its legitimacy to govern and its implications for the identity of Germany’s first democracy, this comparative study evaluates the coverage of war-related issues in a broad range of republican press sources between 9 November 1918 and 6 June 1920. In order to contextualise these 3,626 newspaper and journal articles in their related party-political framework, this research furthermore assesses 327 political leaflets as well as selected contemporary pamphlets, monographs and novels to explain the republican failure to come to terms with the trauma of war.
Keywords: Modern History, Ph.D.; Ph.D. Trinity College Dublin